Imagery as Discourse: Approach to Studies - Savich, Elena (Respectus Philologicus, 2012)
This article is intended to build a procedure for imagery discourse analysis and to apply it to samples of a particular discourse – that of the Polish Solidarity movement. The main assumptions underlying this aim are: that the discourse of a certain historical period keeps its content regardless of the nature of its manifestation and can be traced by analysing the art of the period, and that images are texts and, thus, are subject to text/discourse analysis. To elaborate a research program and to see the categories of such analysis, the author adapts the qualitative research procedure of the Grounded Theory to the study of imagery discourse, combining it with the categories and procedures of the Causal-Genetic Theory. This approach proves that images carry information of two types – thematic and cortege information. The thematic content of an image represents the physical context of historical events, actualizing a certain fragment of reality. The cortege content of an image represents and actualizes the addresser – addressee interaction. In the proposed research program, both of the content/information types are under reconstruction. The whole procedure of imagery discourse analysis is presented as involving multistep categorization on different levels: categorization on the level of visual characteristics followed by categorization on the level of propositions, which in turn presupposes reconstruction of thematic and cortege propositions. Application of this procedure to the analysis of four pieces of art that represent the period of the Solidarity movement in Poland allows conclusions to be drawn about the primary categories of imagery discourse (colour, type of lines, characters and disposition) and their subcategories (opposition, universality, intertextual capacity, photographic accuracy, size and perspective). It also becomes possible to formulate some preliminary conclusions about the typical propositions of the discourse of the Solidarity movement.
Keywords: imagery discourse; discourse picture of the world; discourse picture of communicant interaction; discourse categories; Grounded Theory; Causal-Genetic Theory